Application of ultrasound in chicken breast during chilling by immersion promotes a fast and uniform cooling. (July 2018) - Flores, Diego Rafael Martins; Brasil, Carla Cristina Bauermann; Campagnol, Paulo Cezar Bastianello; Jacob-Lopes, Eduardo; Zepka, Leila Queiroz; Wagner, Roger; Menezes, Cristiano Ragagnin; Barin, Juliano Smanioto; Flores, Erico Marlon Moraes; Cichoski, Alexandre José
Abstract: The initial objective of the study was to evaluate different operation modes (sweep and normal) and frequencies (25 and 130 kHz) of ultrasound in pre-chilling of breast chicken cylinders (BCC) immersed in water at 10 °C during 10 min. The second objective was to study the effect of the immersion time (5, 10, 15, 20, and 30 min) using the best operation mode and frequency obtained in the pre-chilling of the BCC in water at 10 °C. Pre-chilling was evaluated in both stages by infrared thermography, and the percentages of water absorption were determined in the second stage. The application of US at 130 kHz and normal operation mode provided a reduction of temperature on the surface of BBC higher (≈19.6%) than untreated samples. Also, compared to control, the US-treated samples in these conditions presented a more uniform cooling rate (≈22.3%) and higher water absorption (≈113%). Graphical abstract: Highlights: Use of ultrasound bath during pre-chilling process of breast chicken Ultrasound increased rate of cooling of breast chicken Ultrasound promoted a more uniform cooling of breast chicken compared to control. Ultrasound is a viable alternative to reduce time of pre-chiller process.